2021
DOI: 10.3390/agronomy11112267
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Role of Rhizosphere Microbiome and Root Traits in Organic Phosphorus Mobilization for Sustainable Phosphorus Fertilization. A Review

Abstract: Moving toward more sustainable sources for managing phosphorus (P) nutrition in agroecosystems, organic phosphorus (Po) derived from organic inputs and soil is increasingly considered to complement mineral P fertilizer. However, the dynamics of P added by organic input in soil-plant systems is still poorly understood and there is currently no clear information on how the Po composition of these amendments determines P availability through interactions with the soil microbiome and root traits. Here, we review t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 211 publications
(236 reference statements)
0
25
0
Order By: Relevance
“…However, this indicates that the higher adsorption of IHP relative to other OP compounds did not necessarily imply that its binding capacity is always strong and stable under all environmental conditions. Thus, we suggest that despite the higher accumulation of myo-IHP reported in most soils (Amadou et al, 2021;Gerke, 2015), its desorption may be easier than that of the GLY or G6P forms, although this depends greatly on the soil minerals and experimental conditions . Furthermore, our results indicated that if both GLY and G6P species compete with myo-IHP for the same active sites on soil minerals, the binding energy of GLY or G6P would be higher than that of myo-IHP.…”
Section: Influence Of Organic Phosphorus Properties On Adsorption And...mentioning
confidence: 75%
See 3 more Smart Citations
“…However, this indicates that the higher adsorption of IHP relative to other OP compounds did not necessarily imply that its binding capacity is always strong and stable under all environmental conditions. Thus, we suggest that despite the higher accumulation of myo-IHP reported in most soils (Amadou et al, 2021;Gerke, 2015), its desorption may be easier than that of the GLY or G6P forms, although this depends greatly on the soil minerals and experimental conditions . Furthermore, our results indicated that if both GLY and G6P species compete with myo-IHP for the same active sites on soil minerals, the binding energy of GLY or G6P would be higher than that of myo-IHP.…”
Section: Influence Of Organic Phosphorus Properties On Adsorption And...mentioning
confidence: 75%
“…Furthermore, in the presence of different OP forms in soils, the preferential adsorption of myo-IHP or IP over both G6P and GLY may increase G6P and GLY availability and promote their mineralization. Thus, this contrasting adsorption dynamics of OP versus IP have important implications for P management from organic input in soils because IHP, GLY and G6P can comprise up to 80% of total P in some organic input (Amadou et al, 2021;Darch et al, 2014;George et al, 2018), and many animal manures, notably those from monogastrics (pigs, poultry), contain substantial quantities of inositol phosphates (Hu et al, 2020a;Peperzak et al, 1959).…”
Section: Adsorption and Desorption Dynamics Of Op Relative To Ipmentioning
confidence: 99%
See 2 more Smart Citations
“…They have received considerable attention due to their high P adsorption capacity (Bortoluzzi et al, 2015;Ryan et al, 2001) which may causes an OP utilization e ciency in soils as low as 5-10% (He et al, 1994). This leads to poor utilization of OP sources in agroecosystems (Amadou et al, 2021;Sulieman and Mühling, 2021). Indeed, OP compounds adsorbed on minerals were found to be the most stable P forms in different soil types (Martin et al, 2002;Montalvo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%